Effect of Disaster Mitigation Education on Earthquake Preparedness Knowledge among Children with Special Needs - Astuti, Vitaria Wahyu; Richard, Selvia David; Aryanti, Putu Indraswari (Babali Nursing Research, 2025)
Introduction: Earthquakes are natural disasters that frequently occur around us, an event that can be recognized or not recognized by the public, both in general and vulnerable populations, one of which is children with special needs. Children with special needs are at high risk of becoming victims of disasters. This condition can be caused by physical or mental limitations, which affect their knowledge about disasters and how to survive earthquakes. Methods: This study employed a pre-experimental one-group pretest–posttest design involving 39 children with special needs at SLB-B Putera Asih, selected through purposive sampling based on inclusion criteria. Data were collected using a 14-item knowledge questionnaire on earthquake disaster mitigation. The intervention consisted of earthquake disaster mitigation education through role-play simulations and interactive video with sign language support. Data were analyzed using the Wilcoxon Signed Rank Test with a significance level of α = 0.05. Results: After receiving earthquake disaster mitigation education, most children with special needs demonstrated improved knowledge, with 26 students showing an increase, only two students showing a decrease, and 11 students remaining the same. The significance value was p = 0.000, indicating that disaster mitigation education significantly enhanced earthquake preparedness knowledge among children with special needs at SLB-B Putera Asih. Conclusion: Providing earthquake disaster mitigation education through role-play and interactive video significantly increased the knowledge of children with special needs and enhanced their ability to practice self-rescue measures during an earthquake.